A historical account of progress made in cassava varietal improvement in China - Lin, Xiong; Li, Kaimian; Tian, Yinong; Huang, Jie; Xu, Ruili (International Center for Tropical Agriculture, 2001)
Cassava varietal improvement in China has historically been conducted by collecting and evaluating local varieties, by introducing and testing of cassava germplasm from abroad, followed by the establishment of a cassava cross-breeding program. Considerable progresses has been made in the following areas: a) Collection and evaluation of the local varieties, SC205 and SC201 and their extension over a wide range of growing conditions, so as to expand their growing range and planting area b) Setting up a cassava germplasm bank to conduct cross-breeding of cassava c) Establishing a nation-wide cassava regional trial network, which forms an integral part of the breeding program, in order to develop improved varieties, test and demonstrate as well as extent new higher-yielding cassava varieties d) Selection of many promising clones e) Release of some improved varieties. The cassava breeding program in China was started in the 1960s when several good local varieties were collected, evaluated and released. It was shown that cassava can be planted in the region south of Qinling Huaihe and the Yangtse river basin, in those areas having a mean annual temperature above 18o C and a frost-free period of more than 8 months of the year. Since the 1970s marked progress has been made by adopting an integrated system of germplasm introduction and breeding, with the major objectives of high yield, high starch content and resistance to wind. A nation-wide cassava trial network was established to form part of this integrated breeding system to produce improved varieties, test, select and demonstrate as well as extend these new varieties. Some of these improved varieties, such as SC6068, SC124, SC8002, SC8013, Nanzhi-188, GR891 and GR911, have been released. They are now grown in an area of about 50,000 ha and outyield the local clones by about 20%, increasing farmers’ income by more than 3.4 million yuan. In recent years the cassava breeding program in China has been capable of annually producing more than 3000 hybrid seeds from 80-100 cross combinations, as well as evaluating 2000-3000 hybrid seeds introduced from CIAT/Colombia and the Thai-CIAT program. More than 500 promising clones have been selected, of which OMR33-10-4, ZM8641 and ZM9057 will be further tested and examined for release. In addition, many promising clones, such as CMR34-11-4, OMR36-63-6, OMR37-103-1, OMR37-14-9, CMR38-163-4, SM2323-6 and ZM9244, which are characterized by high yield and high dry matter content, can be used in the future in the cassava varietal improvement program in China.